Die impak van die grondwet op godsdiens – ‘n voorlopige waarneming - Malherbe, R (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
In this contribution, the nature and status of supreme constitutions, and the South African Constitution in particular, as well as the role and application of the Bill of Rights, are discussed by way of introduction. An in-depth analysis of the right to freedom of religion is made, and within the constitutional framework the relationship between religion and the state is discussed with reference to applicable case law. The discussion singles out the significant impact of the right to religious freedom on the relationship between religion and the state. An attempt is made to define the relationship between religion and the state and demarcate more clearly the autonomy of religious institutions. Three key aspects of this relationship are highlighted, first, that the right to religious freedom guarantees to religious instiututions a particular field of autonomy, second, that in South Africa a strict wall of separation between religion and the state is not appropriate, and that the state is expected to maintain a healthy, impartial involvement, and third, that the non-entanglement doctrine in terms of which the courts are not supposed to adjudicate on doctrinal issues, forms part of our law. In this regard, issue is taken with the humanistic approach followed by the Constitutional Court in moral issues. Finally, it is argued that religious institutions should act themselves as watchdog over the right to religious freedom and the relationship between religion and the state. The suggestion is made that a charter of religious rights and freedoms could assist in demarcating the relationship between religion and the state more clearly, and facilitate the resolution of sensitive issues.